Instrument for measuring quality of life of employees in the Malaysian public sector - Mahmood, Nor Asiah; Uli, Jegak; Othman, Jamilah; Abu Samah, Bahaman; Ali, Noor Azman; Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril (American-Eurasian Network for Scientific Information, 2011)
Quality of life has been defined in a multitude of ways and there is little agreement on elements that should be measured. The main intent of this paper is to describe the process of developing a valid and reliable instrument for measuring quality of life (QOL) of employees in Malaysian public sector. There are several steps in developing this instrument. Initially literature search was carried out. Nine dimensions of QOL were identified based on the literature reviewed and then an early version of the instrument was drafted. Subsequently, two focus group discussions (FGDs) were organized to review the construct and content validity of the instrument. Ten representatives from selected public sectors agencies participated in the first FGD to review the content validity of the draft instrument. The second FGD focused on the construct as well as the clarity of the language used with the help of 21 representatives from various government agencies. Improvements were made on the final instrument based on the feedbacks received from the experts invited. This final instrument incorporated the following nine dimensions: remunerations and benefits (9 items), job characteristics (8 items), interpersonal relationships (7 items), work environment (9 items), organizational support and facilities (8 items), organization policies and management styles (9 items), safety and security assurance provisions (5 items), individual and family (6 items), and personal health and well-being (9 items). The instrument was tested on 30 employees who were randomly selected from two government agencies. Analysis of the reliability of the instrument shows that the range of Cronbach's Alpha values obtained was from.80 to.98 suggesting excellent reliability.